Refractory spontaneous hypoglycaemia: a diagnostic conundrum. (24th September 2018) - Cheah, Seong Keat; Halsall, David; Barker, Peter; Grant, John; Mathews, Abraham; Seshadri, Shyam; Krishnan, Singhan
Summary: A frail 79-year-old lady with dementia presented with a 2-year history of frequent falls. Recurrent hypoglycaemic episodes were diagnosed and treated with continuous glucose infusion in multiple hospital admissions. Hypoadrenalism and hypothyroidism were ruled out. Whilst hypoglycaemic (blood glucose 1.6 mmol/L), both plasma C-peptide and proinsulin concentrations, were inappropriately elevated at 4210 pmol/L (174–960) and >200 pmol/L (0–7) respectively with plasma insulin suppressed at 12 pmol/L (0–180). Whilst reported cases of proinsulinoma are typically pancreatic in origin, radiological investigations of the pancreas in this patient did not identify abnormalities. Unexpectedly contrast CT identified a heterogeneously enhancing mass (6.6 cm) at the lower pole of the left kidney consistent with renal cell carcinoma. Non-islet cell tumour-induced hypoglycaemia has been associated with renal malignancy; however, a serum IGF2:IGF1 ratio measured at <10 effectively excludes this diagnosis. Concomitantly on the CT, extensive peripherally enhancing heterogeneous mass lesions in the liver were identified, the largest measuring 12 cm. A palliative approach was taken due to multiple comorbidities. On post-mortem, the kidney lesion was confirmed as clear cell renal carcinoma, whilst the liver lesions were identified as proinsulin-secreting neuroendocrine tumours. In conclusion, the diagnosis of proinsulinoma can be missed if plasma proinsulin concentration is not measured at the time of hypoglycaemia. In this case, the plasma insulin:C-peptide ratio was too high to be accounted for by the faster relative clearance of insulin and was due to proinsulin cross-reactivity in the C-peptide assay. In addition, the concomitant malignancy proved to be a challenging red herring. Learning points: Even in non-diabetics, hypoglycaemia needs to be excluded in a setting of frequent falls. Insulin- or proinsulin-secreting tumours are potentially curable causes. Whilst investigating spontaneous hypoglycaemia, if plasma insulin concentration is appropriate for the hypoglycaemia, it is prudent to check proinsulin concentrations during the hypoglycaemic episode. Proinsulin cross-reacts variably with C-peptide and insulin assays; the effect is method dependent. In this case, the discrepancy between the insulin and C-peptide concentrations was too great to be accounted for by the faster relative clearance of insulin, raising the suspicion of assay interference. The C-peptide assay in question (Diasorin liaison) has been shown to be 100% cross reactive with proinsulin based on spiking studies with a proinsulin reference preparation. Whilst reported cases of proinsulinoma and 99% of insulinomas are of pancreatic origin, conventional imaging studies (CT, MRI or ultrasound) fail to detect neuroendocrine tumours <1 cm in 50% of cases. The concomitant renal mass identified radiologically proved to be a red herring. In view of the rarity of proinsulinoma, no conclusive association with renal cell carcinoma can be established.